HUMAN RIGHTS IN THE CONDITIONS OF URBANIZATION - Natalia V. Bocharova (Alfred Nobel University Journal of Law)
World practice proves that one of the important functions of city self-government in recent years has become the provision of management services that meet local needs and priorities related to the realization of human rights at the local level. Although the primary responsibility for the promotion and protection of human rights rests with national governments, the promotion of a culture of human rights at local level plays a vital role in promoting the respect and realization of human rights in society. The article analyzes the connection between the process of urbanization and the process of "municipalization of human rights", which refers to the transfer of human rights activities to the local level, mainly in cities. It is noted that the trends of socio-political and socio-economic development of the late 1980s and early 1990s of the 20th century, associated with the rapid development of large cities and the creation of urban agglomerations, led to the involvement of cities in the discourse and practice of international human rights, when the latter began to be taken into account in the formation of city policy. It is indicated that the involvement of megacities in human rights activities took place against the background of two phenomena, firstly, the emergence of the concept of "human rights cities" and the formation of a corresponding socio-political movement, which quickly acquired an international character, and secondly, the emergence of the doctrine and global movement for the right to the city. The article reveals their essence and significance. The author concludes the need for further theoretical research in the field of doctrinal and practical aspects of the problem of the connection between urbanization and human rights.